In memoriam: Magnus Ljunggren (October 25, 1942 – June 19, 2022) - Hellman, Ben; Bodin, Per-Arne (Slavica Revalensia, 2022)
This is an obituary for Prof. Magnus Ljunggren of the University of Gothenburg (Göteborgs universitet), a distinguished expert in Russian Symbolism and Andrey Bely’s novel Petersburg, who was also an active supporter of the Russian dissident movement and an unequivocal critic of Vladimir Putin’s regime.